Method of adjusting a temperature compensating resistor while it is in a circuit - MERRICK; EDWIN B (1986)
A method of providing a temperature compensating resistor having a desired ohmic change with temperature comprising the steps of connecting a resistor RT that is made of material having a high temperature coefficient in parallel with a resistor RS that is made of material having a lower temperature coefficient, connecting the parallel combination in a circuit and increasing the value of RS by cutting it with a laser until the circuit indicates that the desired result is obtained.